DANCE AND GENDER: POSSIBILITIES OF PHISICAL EDUCATION IN THE SCHOOL (Fiep Bulletin - online, 2014)
This work evaluated the relationship of boys and girls with dance and other expressive activities, and the relationship between male and female pupils with dance. We tried to understand the gender exclusion/interaction in the interaction with dance and the possibilities of dance as a formative and performance contents for both genders at school. The aesthetic education is also considered as pedagogical concept to mediate the gender relationships ant attitudes towards dance in schooling.For this purpose, a phenomelogical and hermeneutics qualitative research was made, trying to understand the elaboration of a reality through the empirical material.The theoretical referential system points out to the aesthetical dimension of education, the phenomelogical and socio-anthropological meaning of dance and the understanding of the historical process of rationalization, that helped to tear apart body and mind, the subjugation of sensibility and the feminine and led to the justification of polarized gender relationships that have an influence in body silencing and in the relationship of men and women with dance.From the understanding of scenes and voices of reality, were revealed the possibilities of gender interaction in the way dance is live and the possibilities of dance as a formative and performance contents for both genders in education.
Keywords: Dance; Gender; Phenomenology